The validity of Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5) as screening instrument with Kurdish and Arab displaced populations living in the Kurdistan region of Iraq - Hawkar Ibrahim; Verena Ertl; Claudia Catani; Azad Ali Ismail; Frank Neuner (BMC Psychiatry, 2018)
Abstract Background The Posttraumatic Stress Disorder Checklist (PCL) is a valid and reliable self-report measure for the assessment of Posttraumatic Stress Disorder (PTSD). Recently the PCL was updated according to the DSM-5 criteria for PTSD. So far only a few studies have examined the psychometric properties of the PCL-5, and all of these are restricted to populations living in industrialized countries. The aim of this study was to determine the psychometric properties and diagnostic utility of the PCL-5 as a screening instrument for war-affected displaced Kurdish and Arab populations. The specific goal was to determine a contextually valid cut-off score for a probable diagnosis of PTSD. Methods The PCL-5 was translated into Arabic and two Kurdish dialects. Trained interviewers administered these translations as assisted self-reports to 206 adults living in camps for displaced people in Iraq, together with depression and war-exposure instruments. Two weeks later, 98 randomly chosen subjects were reassessed by expert clinical psychologists. In the absence of a gold-standard instrument with proven validity in this context, the expert interviewers applied the PCL-5 items in the form of a clinical interview and used a DSM-5-algorithm to determine a diagnosis of PTSD. Receiver operator characteristics (ROC) were performed to determine a valid cutoff-score. Results The internal consistency of the PCL-5 was high (alpha = .85) and the instrument showed an adequate convergent validity. Using the cut-off score of 23, the PCL-5 achieved the optimal balance of sensitivity and specificity (area under the curve = .82, p < .001; sensitivity = .82, specificity = .70). Conclusions Given that the comparison of the two assessments included both a re-test interval and validation by different interviewers, our results indicate that the PCL-5 can be recommended as an assessment and screening instrument for Kurdish and Arab populations.